2018
DOI: 10.1186/s12864-018-4945-x
|View full text |Cite
|
Sign up to set email alerts
|

In-solution Y-chromosome capture-enrichment on ancient DNA libraries

Abstract: BackgroundAs most ancient biological samples have low levels of endogenous DNA, it is advantageous to enrich for specific genomic regions prior to sequencing. One approach—in-solution capture-enrichment—retrieves sequences of interest and reduces the fraction of microbial DNA. In this work, we implement a capture-enrichment approach targeting informative regions of the Y chromosome in six human archaeological remains excavated in the Caribbean and dated between 200 and 3000 years BP. We compare the recovery ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…It is possible that the correlation of capture success with precapture subject DNA proportions may become nonlinear at lower values due to, for example, increased rates of misbinding between baits and library DNA, leading to deviation from our predictions. Although a number of studies focused on ancient DNA provide some evidence that the correlation of capture success with precapture subject DNA proportions holds for lower quality samples (Ávila‐Arcos et al., ; Carpenter et al., ; Cruz‐Dávalos et al., , ), these studies lack the sample sizes needed for statistical tests of this hypothesis. Thus, further experimental work on samples with low proportions of subject DNA are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the correlation of capture success with precapture subject DNA proportions may become nonlinear at lower values due to, for example, increased rates of misbinding between baits and library DNA, leading to deviation from our predictions. Although a number of studies focused on ancient DNA provide some evidence that the correlation of capture success with precapture subject DNA proportions holds for lower quality samples (Ávila‐Arcos et al., ; Carpenter et al., ; Cruz‐Dávalos et al., , ), these studies lack the sample sizes needed for statistical tests of this hypothesis. Thus, further experimental work on samples with low proportions of subject DNA are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the two tissue extracts which serve as high‐quality DNA controls, we chose 110 faecal extracts, each representing a unique individual, for exome sequencing based on their estimated percentage of subject DNA relative to total DNA concentration. Because studies of ancient DNA found that hybridization capture of samples with <1% subject DNA yielded only small amounts of useable data (Ávila‐Arcos et al., ; Cruz‐Dávalos et al., ), we conservatively chose extracts with more than 2% subject DNA. In addition, we only used samples with total DNA concentrations >6 ng/μl so that we could remove 200 ng for library preparation without needing to concentrate the extract.…”
Section: Methodsmentioning
confidence: 99%
“…R. Soc. B 375: 20190580 the cemento-enamel junction [57]. The roots were then covered in aluminium foil and pulverized using a hammer, as in [58].…”
Section: (B) Dna Extraction and Library Preparationmentioning
confidence: 99%
“…Another uniparental marker, the Y-chromosome DNA (Y-DNA), was also used to study aDNA. As each cell possesses only one copy of the Y chromosome, the hybridization capture was carried out to enrich specific genomic regions of the Y chromosome both on solid support ( Fu et al, 2013 ) and in solution ( Cruz Dávalos et al, 2017 ). However, targeting mitochondrial DNA or Y chromosome involves discarding a large proportion of potentially informative sequences present in autosomal DNA.…”
Section: Early Developments Of Hybrid-capture Strategies: Human Genetmentioning
confidence: 99%